Evaluation of vaccines designed to induce protective cellular immunity against the Plasmodium yoelii circumsporozoite protein: vaccinia, pseudorabies, and Salmonella transformed with circumsporozoite gene. - Sedegah, M. (World Health Organization, 1990)
In an attempt to induce a protective cytotoxic T-cell mediated immunity against sporozoites of Plasmodium yoelii, the gene encoding the P. yoelii circumsporozoite (CS) protein was engineered into three live vectors: vaccinia, attenuated pseudorabies, and attenuated Salmonella typhimurium. Balb/c mice were immunized with 1-4 doses of 10(8) pfu of the vaccinia construct (IP), 3 doses of 10(5), 10(6) or 10(7) pfu of pseudorabies construct (IV), and 3 doses of 10(9) salmonella transformants (orally). In the case of vaccinia and pseudorabies constructs, an excellent immune response was obtained as measured by antibodies to sporozoites. No protection or delay in prepatent period was seen in any of the experimental animals when challenged with 200 (vaccinia, pseudorabies) or 100 (salmonella) sporozoites, although mice immunized with irradiation-attenuated sporozoites were consistently protected against challenge with greater than 10(4) sporozoites. Since other vaccinia, pseudorabies, and salmonella CS constructs have been shown to induce cytotoxic T lymphocytes (CTL) against the CS protein, it is likely that CTL against the CS protein were induced during these studies. It is currently unclear if the vaccines did not induce the appropriate CTL or inadequate numbers of CTL, or if CTL against the P. yoelii CS protein are inadequate to protect against sporozoite challenge.